Gay and lesbian literature in the classroom: Can Gay themes overcome heteronormativity? - April M Sanders; Janelle B. Mathis (Journal of Praxis in Multicultural Education, 2013)
Lesbian, gay, bisexual, and transgender (LGBT) characters do exist in children’s and young adult literature, yet there is a lack of classroom exposure to such literature. Educational organizations have realized the need for dispelling prejudices about LGBT people by including such texts in the classroom as well as discussions regarding LGBT themes and characters in the books. Yet the practice of simply including diverse texts without discussing LGBT issues could cause greater marginalization for students because the silence regarding LGBT issues and characters encourages the practice of heteronormativity. This inquiry examined a range of children’s and adolescent books that could be used in classroom discussions to develop insight about LGBT themes and characters in order to understand if the texts were saturated with LGBT themes and characters to the point that teachers and students could not avoid the LGBT factors while reading.
Keywords: amériques; approches et analyses; discipline; hétérosexisme; identités LGBTQIA2+; pédagogie; ressource en ligne; régions géographiques; science de l'éducation; systèmes d'oppressions; thématiques; états-unis

Deconstructing privilege: Teaching and learning as allies in the classroom - Case, Kim (Routledge, 2013)
Although scholarly examinations of privilege have increased in recent decades, an emphasis on privilege studies pedagogy remains lacking within institutions. This edited collection explores best practices for effective teaching and learning about various forms of systemic group privilege such as that based on race, gender, sexuality, religion, and class. Formatted in three easy-to-follow sections, Deconstructing Privilege charts the history of privilege studies and provides intersectional approaches to the topic. Drawing on a wealth of research and real-life accounts, this book gives educators both the theoretical foundations they need to address issues of privilege in the classroom and practical ways to forge new paths for critical dialogues in educational settings. Combining interdisciplinary contributions from leading experts in the field-- such as Tim Wise and Abby Ferber-- with pedagogical strategies and tips for teaching about privilege, Deconstructing Privilege is an essential book for any educator who wants to address what privilege really means in the classroom.
Keywords: amériques; approches et analyses; discipline; intersectionnalité; inégalités; justice sociale; outils; ouvrages de références; privilèges; régions géographiques; sciences de l'éducation; systèmes d'oppressions; états-unis

L’inclusion de la diversité sexuelle à l’école : les enjeux pour les élèves lesbiennes, gais, bisexuels et en questionnement - Richard, Gabrielle; Chamberland, Line; Petit, Marie-Pier (Revue canadienne de l’éducation, 2013)
Cet article s'appuie sur les résultats d'une enquête qualitative menée auprès de 65 jeunes lesbiennes, gais, bisexuels et en questionnement (LGBQ) québécois qui ont témoigné de leurs expériences scolaires en lien avec l'homosexualité. Les entrevues visaient à rendre compte de la place de la diversité sexuelle dans les cours, à relever les façons dont est abordée cette thématique en classe, ainsi qu'à examiner les perceptions qu'ont les participants de ces moments de visibilité. Les jeunes LGBQ rapportent que les sujets relatifs à la diversité sexuelle sont rarement abordés à l'école, mais se souviennent avec force détails de chacune des mentions de ces sujets. Nombre d'entre eux rapportent une vive crainte d'être étiqueté comme homosexuel à l'occasion de telles séances, ou encore de faire l'objet de railleries homophobes par la suite.
Keywords: 2000 à aujourd'hui; 2000-2009; EDI; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; discipline; discours dominant; homophobie; hétérosexisme; identités LGBTQIA2+; périodes historiques; québec; ressource en ligne; régions géographiques; science de l'éducation; systèmes d'oppressions; systèmes éducatifs; thématiques; école; étude qualitative